Effect of hyperbaric oxygen therapy combined with autologous platelet concentrate applied in rabbit fibula fraction healing (Clinics, 2013)
OBJECTIVES: The purpose is to study the effects of hyperbaric oxygen therapy and autologous platelet concentrates in healing the fibula bone of rabbits after induced fractures. METHODS: A total of 128 male New Zealand albino rabbits, between 6-8 months old, were subjected to a total osteotomy of the proximal portion of the right fibula. After surgery, the animals were divided into four groups (n = 32 each): control group, in which animals were subjected to osteotomy; autologous platelet concentrate group, in which animals were subjected to osteotomy and autologous platelet concentrate applied at the fracture site; hyperbaric oxygen group, in which animals were subjected to osteotomy and 9 consecutive daily hyperbaric oxygen therapy sessions; and autologous platelet concentrate and hyperbaric oxygen group, in which animals were subjected to osteotomy, autologous platelet concentrate applied at the fracture site, and 9 consecutive daily hyperbaric oxygen therapy sessions. Each group was divided into 4 subgroups according to a pre-determined euthanasia time points: 2, 4, 6, and 8 weeks postoperative. After euthanasia at a specific time point, the fibula containing the osseous callus was prepared histologically and stained with hematoxylin and eosin or picrosirius red. RESULTS: Autologous platelet concentrates and hyperbaric oxygen therapy, applied together or separately, increased the rate of bone healing compared with the control group. CONCLUSION: Hyperbaric oxygen therapy and autologous platelet concentrate combined increased the rate of bone healing in this experimental model.